Brain/MINDS Beyond Human Brain MRI Project: A Protocol for Multi-Site Harmonization across Brain Disorders Throughout the Lifespan - Koike, Shinsuke; Tanaka, Saori C; Okada, Tomohisa; Aso, Toshihiko; Asano, Michiko; Maikusa, Norihide; Morita, Kentaro; Okada, Naohiro; Fukunaga, Masaki; Uematsu, Akiko; Togo, Hiroki; Miyazaki, Atsushi; et al. (bioRxiv, 2020)
Abstract Psychiatric and neurological disorders are afflictions of the brain that can affect individuals throughout their lifespan. Many brain magnetic resonance imaging (MRI) studies have been conducted; however, imaging-based biomarkers are not yet well established for diagnostic and therapeutic use. This article describes an outline of the planned study, the Brain/MINDS Beyond human brain MRI project (FY2018 ∼ FY2023), which aims to establish clinically-relevant imaging biomarkers with multi-site harmonization by collecting data from healthy traveling subjects (TS) at 13 research sites. Collection of data in psychiatric and neurological disorders across the lifespan is also scheduled at 13 sites, whereas designing measurement procedures, developing and analyzing neuroimaging protocols, and databasing are done at three research sites. The Harmonization protocol (HARP) was established for five high-quality 3T scanners to obtain multimodal brain images including T1 and T2-weighted, resting state and task functional and diffusion-weighted MRI. Data are preprocessed and analyzed using approaches developed by the Human Connectome Project. Preliminary results in 30 TS demonstrated cortical thickness, myelin, functional connectivity measures are comparable across 5 scanners, providing high reproducibility and sensitivity to subject-specific connectome. A total of 75 TS, as well as patients with various psychiatric and neurological disorders, are scheduled to participate in the project, allowing a mixed model statistical harmonization. The HARP protocols are publicly available online, and all the imaging, demographic and clinical information, harmonizing database will also be made available by 2024. To the best of our knowledge, this is the first project to implement a rigorous, prospective harmonization protocol with multi-site TS data. It explores intractable brain disorders across the lifespan and may help to identify the disease-specific pathophysiology and imaging biomarkers for clinical practice. Competing Interest Statement Katsutoshi Murata and Yuta Urushibara are employed by Siemens Healthcare K.K., Tokyo, Japan. The other authors report no financial relationships with commercial interests. Footnotes * In this revision, we carried out additional analyses of test-retest data (N=26), as shown in Fig 8. We also replaced myelin maps used in Fig 3, 7 and 8 to those of non biasfield corrected to clarify the need for future elaboration of preprocessing. Overall, the preliminary test-retest in travelling subjects (N=30) not only demonstrated moderately high reliability and specificity to subject-wise connectome but also an issue to be solved as for correction of transmit field biasfield in future. * Abbreviations DALYs disability-adjusted life years MRI magnetic resonance imaging HCP Human Connectome Project ABCD Adolescent Brain Cognitive Development BPD bipolar disorder MDD major depressive disorder DecNef Decoded Neurofeedback ASD autism spectrum disorder ADNI Alzheimer’s Disease Neuroimaging Initiative AD Alzheimer’s disease MCI mild cognitive impairment PPMI Parkinson’s Progression Markers Initiative PD Parkinson’s disease T1w T1-weighted T2w T2-weighted rsfMRI resting state functional MRI CRHD Connectome Related to Human Disease GLM general linear model TS traveling subject AMED Japan Agency for Medical Research and Development Brain/MINDS Beyond Strategic International Brain Science Research Promotion Program HARP Harmonization protocol DWI diffusion-weighted imaging QC quality control MNI Montreal Neurological Institute MSM multi-modal surface matching GLMM general linear mixed model CIFTI Connectivity Informatics Technology Initiative FEF frontal eye field PEF premotor eye field PSL peri-sylvian language STS superior temporal sulcus NODDI nerite orientation and density imaging